Info-edu-tainment of INSANCITA Journal, Issue of August 2017 - INSANCITA, Editor Journal (ASPENSI, 2017)
INSANCITA:Â Journal of Islamic Studies in Indonesia and Southeast Asia.Â This journal, with ISSN 2443-2776, was firstly published on February 5, 2016, in the context to commemorate the Dies Natalies of HMI (Himpunan Mahasiswa Islam or Islamic Students Association) in Indonesia. The INSANCITA journal has been organized by the Alumni of HMI who work as Lecturers at the HEIs (Higher Education Institutions) in Indonesia; and published by Minda Masagi Press as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. The INSANCITA journal is published twice a year i.e. every February and August.Â Bandung, Indonesia: August 30, 2017.Sri Redjeki Rosdianti, M.M.Pd.Director of Minda Masagi Press in Bandung, West Java, Indonesia.